Analysis of The Design of Thickness Variations of Pressure Cooker Equipment Using A Strainer - Alfan Dabbar Muqaffi; Prantasi Harmi Tjahjanti; Edi Widodo (Jurnal Improsci, 2025)
Background. In micro, small, and medium enterprises (MSMEs) that make pressure milkfish, the majority still use manual pressure cookers, with the pressure showing that the milkfish is cracked, making it less attractive in terms of performance and appearance. Aims. Therefore, the purpose of this research is to design a presto milkfish pot equipped with a filter. The design uses AutoCAD for 2D drawings and SolidWorks software 2023 for 3D. The results obtained have been used to design pressure-cooker equipment with a filter. Methods. The results of the design of pressure cooker equipment using filters with varying pan thicknesses are for Von Mises stress, displacement (shift)/elongation, strain/strain, and Safety Factor (SF). Result. The analysis of all design results was obtained: (a). The results of the Von Mises stress simulation, with varying pressure cooker thickness, show that the wall thickness is directly proportional to the maximum Von Mises stress. So the wall of the pressure cooker with the greatest thickness (3mm) has the maximum voltage value of Von Mises, also the greatest (978.0 MPa), (b).  The results of the pressure cooker elongation/displacement simulation with varying pressure cooker thickness showed that thickness variation was not significant for elongation/displacement. The average elongation/displacement is 0.008468 mm; the result is quite small, indicating that the thickness of the pan is not related to the elongation of the pressure cooker material at a break or a certain limit (c). The results of the pressure cooker strain simulation with the pressure cooker thickness variation, with a value of 0.004613, indicate that the pressure cooker thickness variation is not significant to the pressure cooker strain, because the strain obtained does not cause a change in the shape of the pressure cooker equipment, even though the pressure cooker wall has a different thickness Conclusion. Safety Factor simulation results/ Factor of Safety (FS) pressure cookers with pressure cooker thickness variations it appears that for the pressure cooker thickness variation, all have an acceptable FS, because the value exceeds the value of 1.